The Program “Return With a New History” of the MARQ - Cortés i Garrido, Josep Albert; Sala Pérez, Gema; de las Heras Junco, Santiago (Eikón / Imago, 2019)
The project “Return With a New History” is created thanks to the collaboration between the “Fundación Comunitat Valenciana MARQ”, the Archaeological Museum of Alicante Province and the Alicante Penitentary Centre. The main aim of the programme is to promote accessibility, and encourage the knowledge of the Alicante Province history and the Museums treasures, to male and female groups who are currently in prison, thus converting their time of confinement in a useful manner, in which they can acquire new skills, experiences, knowledge and ideas. The Programme aims to promote knowledge of history and also of the cultural resources made available to it, through the MARQ, as a way of covering formative, recreational and motivational aspects.